Self-Declarative Performance of General Dentists in Prescribing Analgesics and Antibiotics for Patients Requiring Root Canal Treatment - Fatemeh Dibaji; Reza Yazdani; Sara Sajadi; Elahe Mohamadi; Fateme Mohammadian; Mohammad Javad Kharazi Fard (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to determine the self-declarative performance of general dentists in prescription of analgesics and antibiotics for patients requiring root canal treatment (RCT). Materials and Methods: In this cross-sectional study, 400 general dentists participating in the 55th International Annual Scientific Congress of the Iranian Dental Association (2015) were randomly selected, and requested to complete a questionnaire about their performance regarding prescribing analgesics and antibiotics for patients requiring RCT. The frequency and percentage of answers to each question were calculated and reported. Results: The most commonly prescribed analgesics included ibuprofen (100.0%), Gelofen (100.0%), Novafen (68.5%) and acetaminophen (24.8%). After RCT, dentists prescribed ibuprofen (100.0%), Gelofen (98.3%), dexamethasone (35.3%), Novafen (27.3%) and acetaminophen/codeine (15.8%) in decreasing order of frequency. Antibiotic prescription was minimum (48.5%) for cases with painful (moderate or severe) irreversible pulpitis (vital tooth) before the treatment and maximum for cases of pulp necrosis with acute apical periodontitis, edema, and preoperative symptoms (moderate or severe) (97.3%). For non-allergic patients, the most frequently prescribed antibiotics were amoxicillin 500 mg (93.3%), cefixime 400 mg (81.3%), amoxicillin/metronidazole 250 mg (71.8%), co-amoxiclav 265 mg (36.3%) and injectable penicillin (0.5%). For allergic patients, dentists prescribed clindamycin 300 mg (84.0%), cephalexin 500 mg (15.8%), azithromycin 500 mg (13.5%), and erythromycin 500 mg (10.8%). Sex and graduation date had no significant effect on the results (P>0.05). Conclusion: Antibiotic prescription is excessive by general dentists, and their performance regarding the proper and logical prescription of antibiotics in RCT should be improved.